2012
DOI: 10.1007/s40069-012-0018-8
|View full text |Cite|
|
Sign up to set email alerts
|

Tailoring ECC for Special Attributes: A Review

Abstract: This article reviews the tailoring of engineered cementitious composites (ECC), a type of high performance fiber reinforced cementitious composites with a theoretical design basis, for special attributes or functions. The design basis, a set of analytic tools built on micromechanics, provides guidelines for tailoring of fiber, matrix, and fiber/matrix interfaces to attain tensile ductility in ECC. If conditions for controlled multiple cracking are disturbed by the need to introduce ingredients to attain a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(92 citation statements)
references
References 4 publications
0
89
0
3
Order By: Relevance
“…However, to ensure a balance between ultimate strength and strain capacity, optimum volume/weight proportion of different fibers is desired (Ahmed et al, 2007). For static loading conditions, HFRC composites result in better energy absorbing properties compared with that of mono-fiber concrete composites (Chen et al, 1996;Abou El-Mal et al, 2015;Li, 2012). A new type of steel fiber with spiral shape, proposed recently (Xu et al, 2012a(Xu et al, , 2012b, has been found to demonstrate larger displacement capacity and provide better bonding compared to hookedend, deformed and corrugated fibers (Hao and Hao, 2013;Hao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to ensure a balance between ultimate strength and strain capacity, optimum volume/weight proportion of different fibers is desired (Ahmed et al, 2007). For static loading conditions, HFRC composites result in better energy absorbing properties compared with that of mono-fiber concrete composites (Chen et al, 1996;Abou El-Mal et al, 2015;Li, 2012). A new type of steel fiber with spiral shape, proposed recently (Xu et al, 2012a(Xu et al, , 2012b, has been found to demonstrate larger displacement capacity and provide better bonding compared to hookedend, deformed and corrugated fibers (Hao and Hao, 2013;Hao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Based on tests conducted on steel fiber reinforced concrete (SFRC), Wang et al (2008) reported significant influence of steel fibers in the softening region of stress-strain curve as compared to their contributions in the initial elastic modulus. Li andXu (2003, 2009) observed the role of basalt fibers in causing considerable increase in the energy absorption and the deformation capacity of basalt fiber based geopolymeric concrete. Due to the low percentage of fibers, no notable enhancement in dynamic compressive strength was observed.…”
Section: Introductionmentioning
confidence: 99%
“…When the bearing capacity dropped to 85% of the maximum load and not less than the yield load, the columns would fail and the test would be terminated [3]. The experimental apparatus is shown Fig.…”
Section: Tab 3 Strengthening Schemesmentioning
confidence: 99%
“…Among these, green high performance fiber reinforced cementitious composites (GHPFRCC) are a new type of environment-friendly of cement-based composites with attractive characteristics for use in civil applications. These new materials exhibit including extremely remarkable pseudo strain hardening behavior, saturated multiple cracking, ultra-high toughness, and are environmentally sustainable [3,7]. Therefore, GHPFRCC is becoming a preferable repair material to strengthen the mechanical performance of reinforced concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research on it (Rokugo et al 2007;Stang and Li 2004), UHPC exhibits less ductile behavior compared to high ductile fiber-reinforced normal strength grade cementitious composites when the same amount of fiber is incorporated. Typical UHPC contains 2 vol% of steel fibers, whereas high ductile fiber-reinforced normal strength grade cementitious composites presenting excellent tensile strain capacity of more than 2 % includes PVA (polyvinyl alcohol) or PE (polyethylene) fibers in general (Choi et al 2016a, b;Lee et al 2012;Li 2003Li , 2012. Recent research works reported that synthetic fibers could also be applied to UHPC instead of steel fibers.…”
Section: Introductionmentioning
confidence: 99%